Impact of Digital Marketing on Promoting the Local Pharmaceutical Products in Jordan - Al-Assaf, Khaled Tawfiq; Foriki, Mariam Said Mahmoud; Samarah, Tariq; Hindieh, Ayman; Mohammad, Suleiman Ibrahim Shelash; Vasudevan, Asokan; Jiang, LanQing; Al Kurdi, Barween (International Review of Management and Marketing, 2024)
This study aims to explore the impact of digital marketing elements on promoting local pharmaceutical products within the pharmacy sector in Amman city the capital of Jordan. The study identifies specific elements of digital marketing, including social media marketing (SMM), Content marketing, e-mail marketing, and online advertising. The descriptive analytical approach is used. The study population consisted of 1926 pharmacies spread throughout Amman city the capital of Jordan, with a random sample of 320 pharmacies. The research tool used to collect data is a structured questionnaire designed to achieve the study’s objectives. For purposes related to the Jordanian laws issued by Jordan Food and Drug Administration (JFDA) regarding the promotion of pharmaceutical products, the questionnaire is restricted to what concerns non-prescription medications (OTC). The data collected from the study sample is analyzed using statistical packages SPSS Version 21. The study concluded with results showing that digital marketing elements have a significant direct positive impact on promoting local pharmaceutical products. Based on the study results, the study concluded a set of recommendations, the most important of which is that pharmacies need to adopt a holistic approach. This involves seamlessly integrating various digital marketing elements, ensuring a cohesive and synchronized strategy for promoting local pharmaceutical products effectively.